Penggunaan Alat Peraga Omniclock dan Bahan Ajar Pengukuran Waktu untuk Meningkatkan Kualitas Pembelajaran - Rema Wafiqoh Ulya; Ary Fawzi; Supriati (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
This study aims to improve the quality of learning and student learning outcomes in mathematics subject matter of time measurement using Omniclock teaching aids and teaching materials of time measurement in class II SDN 2 Kedungsigigit, Trenggalek Regency. Improving the quality and learning outcomes referred to in this study include two aspects, namely cognitive and affective aspects. This research is a classroom action research carried out in one cycle of two meetings consisting of four stages, namely planning, action, observation and reflection. Students' cognitive instruments use the posttest, students' affective instruments use observation sheets. The results showed that the average quality of student learning in the initial conditions was 1.87 and in the first cycle it increased to 3.45. Student learning outcomes also increase in the implementation of the cycle. In the pre-cycle the percentage of students who passed was 41.7% and in the first cycle it increased by 91.7%